2001
DOI: 10.1046/j.1365-2648.2001.01979.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ communication skills: an evaluation of the impact of solution‐focused communication training

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 23 publications
4
124
0
5
Order By: Relevance
“…Sundman (1997) found that SFBT training resulted in increases in positive statements, greater focus on goals and more shared views between clients and social workers. Bowles et al (2001) found improvements in nurses' willingness to communicate with troubled individuals, increased feelings of adequacy and decreased levels of stress.…”
Section: The 'Miracle Question'mentioning
confidence: 94%
“…Sundman (1997) found that SFBT training resulted in increases in positive statements, greater focus on goals and more shared views between clients and social workers. Bowles et al (2001) found improvements in nurses' willingness to communicate with troubled individuals, increased feelings of adequacy and decreased levels of stress.…”
Section: The 'Miracle Question'mentioning
confidence: 94%
“…In the traditional procurement process, project teams are formed on an ad-hoc basis. Gorse and Emmitt (2007) found that 'work environment' and 'working relationship' among project teams has an influence on the effectiveness of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Goodwin, 1993;Bowles et al, 2001;Stein et al, 2005).…”
Section: Factor 2: Credibility and Background Factormentioning
confidence: 99%
“…[4] It has been emphasized as an essential principle of nursing and multi-professional care. [5] Pejmankhah et al (2008) stated that appropriate communication improved patients' health consequences, reduced medical errors and probable litigations. It has been reported that the cause for most court cases against healthcare professionals was communication failure.…”
Section: Introductionmentioning
confidence: 99%